Penggunaan Media Papan Pintar Untuk Mengetahui Nama-Nama Bangun Datar dan Bangun Ruang Pada Kelas 2 - Yuliana, Ifa Ayu; Reza Rachmadtullah; Feny Rita Fiantika (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
In mathematics, the function of the media to facilitate the learning process is based on the belief that the learning process with the help of the media can improve student learning outcomes to achieve the objectives of learning mathematics. With the use of smart board media, it is expected that students' knowledge and understanding of mathematical concepts will be better and can foster students' interest and motivation to learn mathematics. The use of SmartBoard Learning Media is not only to attract attention so that students can pay attention to the material in it, but this learning Smart Board media is to improve their memory when learning mathematics by building data and constructing space. This research uses a qualitative research type. Data collection techniques in this study were observation and interviews. The subjects of this study were class 2 C teachers and class C students. In this study it can be concluded that by using smart board learning media in the material to recognize the names of flat shapes and shapes, active students respond to learning very well, students can understand, can answer questions given by the teacher. , and interact well during learning.